Mood and Modality in Tim Cook’s Speeches: Tenor of Discourse - Siti Nurani; Mulyadi Mulyadi; Rita Karmila Sari (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
Anderson, W. J. (2006). The phraseology of administrative French: a corpus-based study. International Journal of Corpus Linguistics, 13(1), 128-134.Feng, H., & Liu, Y. (2010). Analysis of interpersonal meaning in public speeches- a case study of Obama’s speech. Journal of Language Teaching and Research.Halliday, M., & Matthiessen. (2004). An Introduction to Functional Grammar 3rd Ed. London: Arnold.Halliday, M., & Matthiessen. (2014). Halliday’s Introduction to Functional Grammar. USA: Routledge.Haratyan, F. (2011). Halliday’s SFL and social meaning. International Conference on Humanities, Historical and Social Sciences.Holmes, J. (2007). An Introduction to Sociolinguistics. London: Longman.Mogalakwe, M. (2006). The use of documentary research methods in social research. African Sociological Review.Nurani, S. (2014). Register analysis of the conversations among petroleum engineers (a case study at PT. Dimas Utama). IJEE, 1(2), 167-188.Nurani, S., Mufliharsi, R., & Yohanna, L. (2014). Linguistic features analysis of the English electronic commerce websites. ENGLISH REVIEW: Journal of English Education, 2(2), 133-144.Nurani, S., Widya, & Harared, N. (2017). Commerce Register Analysis of Minangkabau Vernacular in a Colloquial Conversation: A Sociolinguistics Studies. UHAMKA International Conference on ELT and CALL (UICELL), 1-19.Olateju, M.A., & Yusuf, Y.K. (2006). Backchannel communication in Ola Rotimi’s our husband has gone mad again. Nordic Journal of African Studies, 15(4), 520-535.Sadighi, M. B. (2008). Chomsky’s Universal Grammar and Halliday’s Systemic Functional Linguistics: an appraisal and a compromise. Journal of Pan-Pacific Association of Applied Linguistics, 12(1), 11-28.